(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper entitled The Stone Carvers by Jane Urquhart as a Historical Fiction, in which the author shows the historical perspective of the novel that helps in knowing the historical past. The novel focus on the historical events of First World War along with the fictional town of Shoneval in Ontario. The devastation of the World War I and the construction of the Vimy Ridge in France to commemorate the war veterans re portrayed with evidence from history. Jane Urquhart is an internationally acclaimed Canadian author of seven award winning novels, three poetry books and enormous short stories. This work for study in which the victims of war who lost their loved ones and those who survived physically imputed involved in the construction of the monument. the hard work of the carvers without and selfishness made history to the nation and the whole world. The characters Father Gstir, Walter Allward are fictionalized by the writer from real history. The Vimy Ridge battle and the memorial construction glorifies the nation’s history. Urquhart blends history with fiction to read the work in a historical way and to understand the actual history.